2016
DOI: 10.1016/j.minpro.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the value of x in NH4F·xHF on the digestion of plasma-dissociated zircon

Abstract: Ammonium acid fluoride (NH 4 F·xHF) has been identified as an alternative fluorinating agent for zircon, and may provide a method by which a wide variety of anhydrous metal fluorides can be synthesized. Data on the kinetics of the reaction of NH 4 F·xHF with plasma-dissociated zircon, combined with the thermodynamic parameters, are essential for the development of an industrial process for the production of a precursor for the manufacture of zirconium metal, viz. anhydrous ZrF 4 . The reaction yields (NH 4 ) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…'n Aantal artikels oor die oplossing van silikaatverbindings in ABF is reeds gepubliseer (Andreev et al, 2007a, Andreev et al, 2007b, Du Plessis et al, 2016, Nel et al, 2011, Nhlabathi et al, 2012, Retief et al, 2014 Suurroostereksperimente is uitgevoer tussen 100 °C en 300 °C, met roosterperiodes tussen 15 min en 45 min, 'n suuroormaat tussen 0 % en 20 %, loogroerspoed tussen 100 rpm en 400 rpm, die vas-vloeiverhouding tussen 0.05 g mL -1 en 0.13 g mL -1 , en die loogperiode tussen 10 min en 40 min.…”
Section: Materiale En Reagenseunclassified
“…'n Aantal artikels oor die oplossing van silikaatverbindings in ABF is reeds gepubliseer (Andreev et al, 2007a, Andreev et al, 2007b, Du Plessis et al, 2016, Nel et al, 2011, Nhlabathi et al, 2012, Retief et al, 2014 Suurroostereksperimente is uitgevoer tussen 100 °C en 300 °C, met roosterperiodes tussen 15 min en 45 min, 'n suuroormaat tussen 0 % en 20 %, loogroerspoed tussen 100 rpm en 400 rpm, die vas-vloeiverhouding tussen 0.05 g mL -1 en 0.13 g mL -1 , en die loogperiode tussen 10 min en 40 min.…”
Section: Materiale En Reagenseunclassified
“…A literature review showed that ammonium fluorides can be considered as the main reagents for processing chemically stable oxides and other oxygen-containing compounds. Well known is the use of a melt of ammonium fluorides as a reagent for processing the most chemically stable oxygen-containing compounds and also minerals (tantalite, 11 laterite, 12 monazite, 13 spodumene, 14 trinitite, 15,16 zircon, [17][18][19][20][21][22] ilmenite, 23 titanomagnetite, 24,25 polymetallic slags, 26 etc.) and pure oxides (plutonium dioxide, 27 thorium dioxide, 28 lanthanum, neodium and gadolinium, 29 etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The industrial application of ore stripping processes in plasma has been put into practice in various countries around the globe. For example, the South African Atomic Energy Corporation has developed a plasma process by which zircon, ZrSiO 2, may be subjected to phase dissociation at temperatures above 1700 • C [15]. The product of zircon dissociation is zirconium (IV) oxide and silicon (IV) oxide, a reaction which occurs when zircon is heated in a plasma flow, as a highly dispersed powder.…”
Section: Introductionmentioning
confidence: 99%